Preparation and characterisation of activated carbon from agricultural wastes - Rengaraj S; Arabindoo Bhanumathi; Murugesan V
Solid waste disposal has become a major problem in India. Either it has to be disposed safely for the recovery of valuable materials. As agricultural wastes like myrobalan, rubber seed coat, cahewnut sheath, palm seed coat, palm tree flower and pongam sedd coat comprise of cellulose and lignine, they may act as good absorbents. Therefore these wastes have benn exploited for the preparation of activated carbon employing various techniques. Their characterisation studies such as bulk density, moisture content, ash content, fixed carbon content, matter soluble in water, matter soluble in acid, pH, decolourising power, phenol number, ion exchange capacity, iron content and surface area have been carried out to assess the suitability of these carbons as adsorbents in the treatment of water and wastewater. The results obtained show them to be good adsorbents for both organics and inorganics. The present study reveals the recovery of valuable adsorbents from readily and cheaply available agricultural wastes.
Keywords: Activated carbon; Agricultural wastes; Rubber seed; Seed coat